Family Health Strategy: assessment and reasons for searching of health service by users - doi:10.5020/18061230.2011.p347 - Loeste de Arruda Barbosa; Ticiano Magalhães Dantas; Cleide Correia de Oliveira (Universidade de Fortaleza, 2012)
Objective: To assess the evaluation of the users regarding the family health services and identify the main reasons that led them to seek such services. Methods: A descriptive study with qualitative approach, carried out in 5 Family Health Units with 25 users of the Family Health Strategy (FHS) of the city of Crato-CE, Brazil. The study took place from March to April 2009. Semi-structured interview was applied and recorded. We used the technique of thematic content analysis. Results: We found that the users of the FHS have great dissatisfaction, especially on the organization and access to health services, evaluating the family health as inefficient, although bringing care closer to the population, primarily through home visits. It was clear also that there is a search to the service mainly supported by curative vision and the acquisition of medicines. Conclusions: The subjects evaluate the organization and access to healthcare services as unsatisfactory, but value the actions, when there is a bond with the health team. However, there is still demand for health services, based on the search for medicines and medical consultation. Thus, it is necessary to improve services of the Family Health Strategy in Crato, with a view to ensure quality, accessibility and greater resolution of health services.